2023
DOI: 10.1177/2156759x231163525
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Latinx College Students' Experiences With High School Counselors

Abstract: Only a few researchers have used qualitative methods to explore Latinx students' experiences and testimonials with their high school counselors. These studies, conducted more than 10 years ago, found that Latinx students reported negative experiences with high school counselors, such as low academic expectations and lack of availability. In the current study, we interviewed eight Latinx college students from the southern United States to learn about their experiences with their high school counselors. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Emily's account demonstrates that her children were her source of resilient resistance to earn a college degree. Her convictions contradict widely held beliefs that mothers cannot be successful in school (Beeler, 2016) and that Latinas do not value education (see Cavazos et al, 2009). At the intersection of race and gender, Emily's sense of marianismo and apoyo serve as moral strength for her to be a good role model for her children through sacrifice and persistence.…”
Section: Race- Class- and Gender-informed College-going Expectationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Emily's account demonstrates that her children were her source of resilient resistance to earn a college degree. Her convictions contradict widely held beliefs that mothers cannot be successful in school (Beeler, 2016) and that Latinas do not value education (see Cavazos et al, 2009). At the intersection of race and gender, Emily's sense of marianismo and apoyo serve as moral strength for her to be a good role model for her children through sacrifice and persistence.…”
Section: Race- Class- and Gender-informed College-going Expectationsmentioning
confidence: 90%
“…Historically, many Latinas have encountered negative expectations from educators about their chances of graduating from high school and attending college in the United States (Cavazos et al, 2009). Research has since demonstrated that these negative expectations are rooted in racist ideologies regarding Latinas’ alleged cultural, economic, and environmental “deficiencies” (Davis & Museus, 2019).…”
mentioning
confidence: 99%
“…As one of the fastest‐growing groups in the United States (U.S. Census Bureau, 2020), the Latine population has the potential to influence the higher education landscape positively (Cruz et al., 2021). Because a college degree is linked with economic, family, and community stability (Contreras & Contreras, 2015; Vela, Guerra, et al., 2023), understanding factors that help Latine students access and succeed in higher education institutions is important. However, Latine students’ college persistence and graduation rates continue to fall behind their non‐Latine peers (Cruz et al., 2021; Perez Huber et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…High school counselors have a responsibility to support and cultivate academic, career, and social/emotional development among all students, particularly Latine students (e.g., Arriero & Griffin, 2018; ASCA, 2019; CACREP, 2023; Ryu et al., 2021; Tello & Lonn, 2017; Vela, Guerra, et al., 2023). Also, the ASCA Ethical Standards (ASCA, 2022) indicate that school counselors should “promote equity and inclusion through culturally affirming and sustaining practices honoring the diversities of families” (p. 6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation